Comparison of Lake and River Fishery Performance between Two Strains of Steelhead in Eastern Lake Michigan. (25th September 2018) - Prichard, Carson G.; Dexter, James L.; Ledet, Neil D.; O'Neal, Richard; Wolgamood, Martha; VanAmberg, Jan P.; Jonas, Jory L.
Abstract: Management of fish species for which alternative genetic strains can be considered should be informed by indicators of strain‐specific fishery performance. We compared how two strains of steelhead Oncorhynchus mykiss supported indices of angler satisfaction (catch rate and size) and motivation (effort) in the Lake Michigan basin. We assessed 10 years of recreational angling data collected for the Little Manistee River steelhead strain (LMR‐STS) and Skamania steelhead strain (SKA‐STS), which were tagged and stocked as paired groups in the St. Joseph and Manistee rivers. The LMR‐STS were stocked to enhance fall/winter and spring river fisheries, and SKA‐STS were stocked to create river/inshore summer fisheries; both were also intended to contribute to the recreational fishery of Lake Michigan. Summer angler effort exceeded spring effort on the St. Joseph River, whereas spring effort exceeded summer effort on the Manistee River. In spring river fisheries, catch rates of LMR‐STS were higher than those of SKA‐STS. In summer fisheries on the Manistee River, catch rates of SKA‐STS exceeded those of LMR‐STS. In summer on the St. Joseph River, catch rates of LMR‐STS and SKA‐STS were equivalent. In spring/summer, steelhead of either strain stocked in the St. Joseph River were caught equally among eight of nine ports surveyed. The CPUE of Manistee River‐stocked SKA‐STS was higher than that of LMR‐STS in the Lake Michigan fishery. Catch statistics in both rivers and in Lake Michigan indicate that the two strains provide similar opportunities for trophy‐sized steelhead. Our findings suggest that LMR‐STS are favored for the St. Joseph River fishery and may represent a better total return on investment in the Lake Michigan basin.